ANXIETY AND DEFENSE MECHANISM OF THE MAIN CHARACTER IN “THE BLACK CAT” SHORT STORY - Wulidha Mahfuroh Andriana; Teguh Kasprabowo (Universitas Stikubank (UNISBANK) Semarang, 2020)
This research primarily aims to analyze the psychological aspects of the main character in The Black Cat short story. This study, used Psychoanalysis theory by Sigmund Freud to analyze the short story, to find out the anxieties and defense mechanisms used by the main character. Qualitative method was equipped in this study. The data was taken from The Black Cat short story by Edgar Allan Poe. In this study, the main character showed many psychological problems in shape of anxiety. The Main character showed Neurotic, Realistic, and Moral Anxiety. This study also revealed several types of ego defense mechanisms used by the main character to overcome his anxieties. They are: Displacement, Denial, Acting Out, Symbolization, and Projection Defense Mechanism. Keyword: Psychoanalysis, Anxiety, Defense Mechanism, The Black Cat short story.